PERFORMANCE IMPROVEMENT OF GILGEL GIBIE I – MEKELLE TRANSMISSION NETWORK USING OPTIMAL PLACEMENT OF REACTIVE POWER COMPENSATORS - Atnafu, Ermias; Singh, N.P. (Zede Journal of Ethiopian Engineers and Architects, 2023)
This paper presents determination of optimal location, size and type of reactive power compensators for the 19 bus Ethiopian Electric Power Corporation (EEPCo) transmission network running from Gilgel Gibie to Mekelle using Genetic Algorithm (GA). The objective is to determine the optimal location and size as well as type of reactive power compensators so that the power transfer capacity and transmission efficiency of the network is maximized while keeping the bus voltages, reactive power generation/absorption at each bus and line flows within their secure limits. The efficiency of the proposed technique is demonstrated through simulation studies. The performance of the compensated network is compared with that of the uncompensated network. The proposed approach maximizes the power transfer capacity and improves the transmission efficiency as well as the voltage profile of the network as compared to that of the uncompensated network under normal loading and 50% overloading conditions. Moreover, the proposed compensation technique permits a secured 100% overloading of the transmission network whereas the uncompensated network will result in system blackout because of voltage collapse under 100% overloaded operation